Assessment of bacteria exposure in vitro activity to 1st, 2nd, 3rd and 4th generation-cephalosporins and Comparison effects - K. Salim, Dunia; A. Altif, Ibraheem; H. Abdulwahab, Marwa (Tikrit Journal of Pharmaceutical Sciences, 2023)
The emergence and spread of resistance to cephalosporin generations are threateningto create species resistant to all currently available agents. Recently, we have seen thedevelopment and spread of bacteria carrying metallo-betalactamase genes that areresistant to cephalosporins (and all beta-lactams). This study was designed tocomparison the effects of first, second, third and fourth- generation-cephalosporin ondifferent bacterial species, which include: Escherichia coli, Enterobacter cloacae,proteus mirabilis, Klebsiella pneumonia, Pseudomonas aeruginosa, Streptococcuspneumonia and Staphylococcus aureus. 11 cephalpsporins antibiotics were used inthis study, which include: cefalexin, cefazolin, cephalothin, cefuroxime, cefoxitin,cefaclor, ceftibuten, cefotexime, ceftazidime, cefpirome and cefepime. kirby bauermethod was used to detect the activity of these antibiotics in vitro. Results showedthat cefpirome and cefepime antibiotics belonging to 4th generation cephalosporin,exhibit antibacterial spectrum effective, except Str. pneumonia and K. pneumonia.Some cases, 1st generation cephalosporin exhibit more antibacterial spectrum effectivethan other cephalosporin generation. In conclusion. This study indicated thatinsignificant influence among four cephalosporins generation on different bacterialspecies. Although, cephalosporins antibiotics have variant activity against differentbacterial species, but the resistant development among bacteria become the publicproblem during the past 2 decades.